Prognostic factors in advanced pancreatic cancer patients receiving second-line chemotherapy: a single institution experience - Bittoni, Alessandro; Pellei, Chiara; Lanese, Andrea; Giampieri, Riccardo; D’Angelo, Andrea; Giglio, Enrica; Cantini, Luca; Meletani, Tania; Baleani, Maria Giuditta; Berardi, Rossana (Translational Cancer Research; Vol 7, No 5 (October 31, 2018): Translational Cancer Research, 2018)
Background: First-line chemotherapy in pancreatic ductal cancer has been shown to improve the survival and quality of life, while there is still no consensus concerning the role and the optimal regimen for second-line chemotherapy. The aim of our study was to identify prognostic factors that could predict which patients may receive benefit from second-line treatment. Methods: Data regarding 144 patients, with progressive disease after first-line chemotherapy and measurable or evaluable disease, who received second-line chemotherapy were collected. The regimens included capecitabine, 5-fluorouracil (5-FU) or 5-FU based combinations, gemcitabine or gemcitabine-based combinations, nab-paclitaxel or taxanes. Prognostic variables examined were gender, ECOG PS, stage of disease, metastatic localization, presence or absence of peritoneal involvement, surgery on the primary tumor, age, hemoglobin levels (Hb), neutrophil-lymphocyte ratio (NLR), carbohydrate antigen 19-9 (Ca 19-9), lactate dehydrogenase (LDH), sodium (Na+) levels, mono-chemotherapy vs. combination therapy and PFS after first line chemotherapy. Results: The median OS was 5.26 months (95% CI, 4.01–6.84 months) while median PFS was 2.76 months (95% CI, 2.50–3.22 months). At multivariate analysis, three clinical-laboratoristic features (ECOG PS, CA 19-9 value and LDH value) resulted significant independent prognostic factors for OS, with a hazard ratio (HR) respectively of 1.94 (95% CI, 1.18–3.19), 2.99 (95% CI, 1.37–6.54; P=0.006) and 2.10 (95% CI, 1.08–4.04; P=0.029). No significant impact on prognosis was observed for the other variables. Conclusions: This study confirms the role of CA 19-9 in second line setting and highlights the potential role of LDH, as a prognostic relevant factor in this disease. Main limitation of the study is the small percentage of patients treated in first line with intensified regimens such as FOLFIRINOX or gemcitabine and nab-paclitaxel.